Variable rate inorganic foliar fertilization effect on paddy leaves chlorosis, plant growth and yield performance - Abd. Kharim, Muhammad Nurfaiz; Wayayok, Aimrun; Abdullah, Ahmad Fikri; Mohamed Shariff, Abdul Rashid (Taylor and Francis Group, 2022)
Foliar feeding has been growing in popularity and has been used to supplement the soil-based fertilizer applications to enhance the growth and yield of crops. However, spraying a high concentration of foliar fertilizer can cause a leaf burn effect while a low concentration of fertilizer application can show symptoms of nutrient deficiencies on the leaf. This study was conducted to determine the effect of foliar fertilization on paddy leaf chlorosis and its impact on plant growth and yield performances between variable rate application (VRA) and uniform rates of supplying the fertilizer. The experiment was performed for two planting seasons and had four nitrogen (N) treatments (50% fixed rate, 100% fixed rate, 150% fixed-rate, and VRA) that arranged in a randomized complete block design (RCBD) with four replications. Paddy leaf chlorosis counts, plant growth (plant heights, number of tillers, number of panicle and flower), and yield performances (grain yield, number of grains, 1000-grain weight, and number of spikelets) were collected and recorded. The results showed no sign of leaf burns, however, showed chlorosis condition on the paddy leaves for all the treatments. VRA had the lowest chlorosis counts and had the highest SPAD readings at every planting stage for both planting seasons. While for plant growth performance, VRA showed moderate plant heights however had a higher number of tillers, panicle, and flowers compared to uniform rate treatments. So, VRA significantly produced more yield compared to uniform rates in both planting seasons. Therefore, foliar fertilization of VRA performed better compared to the uniform rate treatments.